Seismic behavior of double-skin composite wall with L-shaped and C-shaped connectors. (September 2019) - Chen, Lihua; Wang, Shiye; Lou, Yu; Xia, Dengrong
Abstract: To meet the requirements of good seismic behavior, rapid assembly, and economic feasibility for a high-rise steel residential apartment, the authors developed two innovative double-skin composite walls (DSCWs) with L-shaped and C-shaped connectors. DSCWs are composed of concrete-filled double steel faceplates, which are divided into several compartments by connectors and two boundary columns filled with concrete at the ends of the composite wall. In this paper, eight DSCWs were tested under cyclic loads to investigate the seismic behavior of these new composite walls considering the effect of low axial compression ratio and spacing-to-thickness ratio. Results show that no significant buckling of steel faceplates was observed before the peak load was reached. No obvious pinching effect was observed on the hysteresis curves for all specimens. Ultimate drift ratio ranged from 1/59 to 1/45, and the ductility coefficients varied from 2.45 to 3.80. The equivalent viscous damping coefficient versus drift ratio curves were close to an exponential distribution, and all specimens exhibited great energy dissipation capacity. The strain on connectors was below the yield strain throughout the experimental process, indicating the connectors have a good working performance. Finally, formulas were established for calculating the load-carrying capacity. Highlights: Two innovative double-skin composite walls are presented and the construction process is relatively expedient and practical. The DSCW specimens had good deformation capacity and ductility. Increasing the axial compression ratio could enhance the load-carrying capacity of specimens. The DSCW specimens with a lower S/ts ratio had a higher load-carrying capacity and ductility. The L-shaped and C-shaped connectors exhibited a good working performance. Formulas were established for calculating the load-carrying capacity of DSCW and it can give satisfactory predictions.